Postoperative serum myoglobin as a predictor of early allograft dysfunction after liver transplantation - Zhang, Jin; Han, Yuzhen; Ke, Shuhao; Gao, Rongyue; Shi, Xiaocui; Zhao, Song; You, Pan; Jia, Huimiao; Ding, Qi; Zheng, Yue; Li, Wenxiong; Huang, Lifeng (Frontiers in Surgery, 2022)
Abstract: Background: Early allograft dysfunction (EAD) is a common post-liver transplant complication which has been associated with graft failure and risk for poor prognosis. There are many risk factors about incidence of EAD after liver transplantation (LT). This study was expected to investigate whether elevated postoperative myoglobin (Mb) increases the incidence of EAD in liver transplanted recipients. Methods: A total of 150 adult recipients measured Mb within three days after liver transplantation between June 2019 and June 2021 were evaluated. Then all patients were divided two groups: EAD group and non-EAD group. The univariate and multivariate logistic regression analysis and receiver operating characteristic curve (ROC) were performed. Results: The incidence of EAD was 53 out of 150 patients (35.3%) in our study. Based on multivariate logistic analysis, the risk of EAD increased with elevated postoperative Mb (OR=1.001, 95% CI 1.000 to 1.001, P=0.002). The Mb AUC was 0.657, and 0.695 when combined with PCT. When subgroup analysis was conducted, the AUC of serum Mb prediction was better in patients whose preoperative MELD15 or operative time10h (AUC=0.751, 0.758, respectively, or 0.760, 0.800 when combined with PCT). Conclusion: Elevated Mb significantly increased the risk of postoperative EAD suggesting that postoperative Mb may be a novel predictor for EAD after liver transplantation.